1999
DOI: 10.1007/s004410051238
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nitric oxide synthase isoforms (NOS II and NOS III) in adult rat lung in hyperoxic pulmonary hypertension

Abstract: Breathing air with a high oxygen tension induces an inflammatory response and injures the microvessels of the lung. The resulting development of smooth muscle cells in these segments contributes to changes in vasoreactivity and increased pulmonary artery pressure. This in vivo study determines the temporal and spatial expression of endogenous endothelial nitric oxide synthase (NOS III) and inducible NOS (NOS II), important enzymes regulating vasoreactivity and inflammation, in the adult rat lung during the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 55 publications
2
27
1
Order By: Relevance
“…In accordance with previous observations (Asano et al, 1994;Steudel et al, 1999;Tracey et al, 1994;Watkins et al, 1997), iNOS expression was noted in bronchial epithelial cells of large and small airways. Such prominent constitutive iNOS expression in the bronchial epithelium may reflect the fact that this epithelium represents a barrier with a large external surface, being naturally exposed to airborne noxious and microbial agents even in the absence of lung infection.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In accordance with previous observations (Asano et al, 1994;Steudel et al, 1999;Tracey et al, 1994;Watkins et al, 1997), iNOS expression was noted in bronchial epithelial cells of large and small airways. Such prominent constitutive iNOS expression in the bronchial epithelium may reflect the fact that this epithelium represents a barrier with a large external surface, being naturally exposed to airborne noxious and microbial agents even in the absence of lung infection.…”
Section: Discussionsupporting
confidence: 93%
“…Such prominent constitutive iNOS expression in the bronchial epithelium may reflect the fact that this epithelium represents a barrier with a large external surface, being naturally exposed to airborne noxious and microbial agents even in the absence of lung infection. In addition, iNOS was expressed in bronchial smooth muscle cells, myocytes of pulmonary hilar veins (this study ;Steudel et al, 1999), alveolar macrophages, cells within the BALT, and VSMC of partially and fully muscular vessels (this study). Microdensitometry of immunohistochemical staining intensity showed the most intensive iNOS expression in control lungs to be present in bronchial epithelial cells of large bronchi and in myocytes of large hilar veins.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Recent reports have shown that hyperoxic conditions can result in up-regulation of NOS (37)(38)(39)(40). This notion raises the possibility that hyperoxia provided protection from L-NAMEinduced teratogenesis by modulating NO synthesis, although evidence for oxygen-mediated NOS up-regulation in embryonic or fetal tissues is (to our knowledge) lacking.…”
Section: Tiboni Et Almentioning
confidence: 99%
“…Although iNOS (113) and reactive nitrogen oxide intermediates (114) are elevated in hyperoxia and may participate in hyperoxiainduced lung injury, it is apparent that under appropriate conditions NO (including iNOS-derived NO) may limit hyperoxic lung injury (115). In this regard: (1 ) inhalation of NO has been shown to reduce hyperoxia-induced apoptosis in lungs of intact animals (116), (2 ) pharmacologic inhibition of NO synthesis exacerbates hyperoxic injury (117), and (3 ) iNOS null mutant mice have enhanced inflammation (accumulation of neutrophils) early in the course of hyperoxia (118).…”
Section: No and Acute Lung Injurymentioning
confidence: 99%